PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ASUS (Studi Kasus Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Stikubank (Unisbank) Semarang) (Students' Journal of Economic and Management, 2015)
The purpose of this study was to analyze the effect of product quality and brand image on purchase decisions Asus laptop. The population in this study were students of the Faculty of Economics and Business, University of Stikubank (Unisbank) Semarang, which in 2014 amounted to 1699 students. Samples were selected from students who purchase and or use the Asus laptop. Determination of the number of samples by using the formula Slovin. Based on this formula, the number of samples in this study defined as many as 100 students. Data collected by using a questionnaire. Data already collected then tabulated and tested by using validity and reliability. After fulfilling the criteria of valid and reliable, the multiple regression analysis to obtain information influence of each independent variable on the dependent variable. The results showed, that the quality of the product is not positive and significant impact on purchasing decisions Asus laptop, while the brand image positive and significant impact on purchasing decisions Asus laptop. The results of this study are still too low to explain the factors that influence the purchase decision, because only limited to two independent variables, while it was still a lot of other variables that can influence purchasing decisions. In addition, this study only examined students into consumers Asus laptop at the Faculty of Economics and Business Unisbank Semarang. Therefore, it is advisable to subsequent researchers to add other variables, as well as increase the population and the sample so much more. Keywords: product quality brand image and purchase decisions.